Successful and safe use of Q‐switched lasers in the treatment of nevus of Ota in children with phototypes IV–VI. Issue 1 (13th November 2017) - Belkin, Daniel A.; Jeon, Hana; Weiss, Elliot; Brauer, Jeremy A.; Geronemus, Roy G.
Abstract : Objective: Nevus of Ota represents congenital dermal melanocytosis in a trigeminal distribution, most commonly occurring in Asian individuals and other individuals with skin of color. Evidence suggests early treatment is beneficial. Multiple reports have shown efficacy and safety of Q‐switched laser treatment in adults. There is little data on children and in non‐Asian skin types. This series was done to demonstrate safe and effective use of Q‐switched laser therapy in children of multiple skin types. Study Design: Retrospective case series. Methods: This was a chart review of patients under 18 years old who presented to our practice from 2002 to 2015 with a clinical diagnosis of nevus of Ota who were treated with Q‐switched lasers (694 and 1, 064 nm). Patients were treated without the use of general anesthesia or sedation, and corneal shields were used in appropriate cases. Percentage of improvement as well as side effects were rated by five physicians independently. Improvement, when present, was rated in quartiles (1–25%, 26–50%, 51–75%, and 76–100% improvement). Results: Twenty‐four children were included. The average age at the start of treatment was 3.9 years old (range of 3 months to 12.4 years), and patients had Fitzpatrick skin types IV through VI. The mean number of treatments was 9.3. Assessment revealed excellent response (76–100% improvement) in 70% of patients and good to excellent response (51–100% improvement) in 86%. Two patients (8%) had post‐inflammatory hyperpigmentation, one of whom also had focal hypopigmentation. Conclusion: Treatment of nevus of Ota with Q‐switched lasers in children with skin of color, without general anesthesia or sedation, is safe and effective. Early intervention should be encouraged for better efficacy and to prevent psychosocial distress in later childhood and adulthood. Lasers Surg. Med. 50:56–60, 2018. © 2017 Wiley Periodicals, Inc.